Studies on Fluorescence Efficiency and Photodegradation of Rhodamine 6G Doped PMMA Using a Dual Beam Thermal Lens Technique. Issue 2 (2002) - Kurian, Achamma; George, Nibu A.; Paul, Binoy; Nampoori, V. P. N.; Vallabhan, C. P. G.
Abstract : In this paper we report the use of the dual beam thermal lens technique as a quantitative method to determine absolute fluorescence quantum efficiency and concentration quenching of fluorescence emission from rhodamine 6G doped Poly(methyl methacrylate) (PMMA), prepared with different concentrations of the dye. A comparison of the present data with that reported in the literature indicates that the observed variation of fluorescence quantum yield with respect to the dye concentration follows a similar profile as in the earlier reported observations on rhodamine 6G in solution. The photodegradation of the dye molecules under cw laser excitation is also studied using the present method.